Teacher Quality Development Strategy through School-Based Management: A Qualitative Literature Review of Best Practices in Various Countries - Ahmad Muktamar (Gestion Educativa, 2025)
This study aims to analyze strategies for developing teacher quality through the implementation of School-Based Management (SBM) using a literature review method that focuses on best practices from various countries. This study highlights the need to strengthen institutional capacity, manage autonomy, and update teacher professional competencies as the main foundation for improving the quality of learning. The analysis shows that SBM provides strategic space for schools to prioritize competency improvement based on the specific needs of students and the dynamics of the learning environment. Literature findings confirm that ongoing training, constructive academic supervision, and collaborative learning communities play a significant role in driving teacher performance improvement. Best practices from various countries demonstrate a consistent pattern of success in schools that are able to integrate autonomy, accountability, and innovation in managing educational quality. This study concludes that SBM has the potential to strengthen pedagogical knowledge renewal through data-driven decision-making mechanisms, targeted professional development, and continuous evaluation of learning quality. This research provides a conceptual contribution to strengthening the model for improving teacher competency based on school management and opens up opportunities for developing implementation strategies in diverse educational contexts.